2018
DOI: 10.1155/2018/3708901
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Conduction and Charging Mechanisms in Atomic Layer Deposited Multilayered HfO2/Al2O3 Stacks for Use in Charge Trapping Flash Memories

Abstract: Method for characterization of electrical and trapping properties of multilayered high permittivity stacks for use in charge trapping flash memories is proposed. Application of the method to the case of multilayered HfO 2 /Al 2 O 3 stacks is presented. By applying our previously developed comprehensive model for MOS structures containing high-dielectrics on the − characteristics measured in the voltage range without marked degradation and charge trapping (from −3 V to +3 V), several parameters of the structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…9,10 C. Zhu et al have already demonstrated that the incorporation of Al 2 O 3 sub-layers into HfO 2 films can obtain larger memory window, improved P/E efficiency, and better data retention for memory devices. 11 Therefore, intensive mixing of HfO 2 and Al 2 O 3 can induce strong inter-diffusion at the interface of these two high-κ dielectrics, thus improving the charge trapping performance of memory devices.…”
mentioning
confidence: 99%
“…9,10 C. Zhu et al have already demonstrated that the incorporation of Al 2 O 3 sub-layers into HfO 2 films can obtain larger memory window, improved P/E efficiency, and better data retention for memory devices. 11 Therefore, intensive mixing of HfO 2 and Al 2 O 3 can induce strong inter-diffusion at the interface of these two high-κ dielectrics, thus improving the charge trapping performance of memory devices.…”
mentioning
confidence: 99%